PILIHAN KARIR BERDASARKAN MODEL SCHWARTZ DAN SCHEIN PADA WIRAUSAHA MUDA DI KOTA BANJARMASIN (TINJAUAN DESKRIPTIF) - Husnurropiq . Husnurropiq; Basuki . Basuki; Azahraty . Azahraty (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2024)
Nowadays career choices are dynamic and changeable, along with the advancement of technology. Business can be done virtually so that it is more attractive to young people. However, Values play an important role in career choice and lifelong career management. Values are the desired goals that individuals seek to fulfill their needs and are important for understanding career orientation in terms of protean and boundaryless career orientations and career anchors. However, how career orientations or career anchors fit into established and supported models and into the structure of human basic values remains an important and under-explored question. The purpose of this study is to use Schwartz's structural values model to empirically explore the relationships and structural correspondences between basic values, career orientations, and career anchor models.Schwartz's value structure. Protean and boundaryless career orientations are positively related to Schwartz's basic values that emphasize openness to change and career anchors meaningfully follow the motivational sequence of these basic values.Overall, the overlap between core values, career orientations, and career anchors emerged as relatively significant, suggesting that core values, orientations, and career anchors should be considered simultaneously to understand and address the factors and processes underlying young entrepreneurs' career choices and paths.